Determination of lower cut‐off levels of adalimumab associated with biochemical remission in Crohn's disease. Issue 3 (6th October 2019) - Carlsen, Arne; Omdal, Roald; Karlsen, Lars; Kvaløy, Jan Terje; Aabakken, Lars; Steinsbø, Øyvind; Bolstad, Nils; Warren, David; Lundin, Knut Erik Aslaksen; Grimstad, Tore
Abstract : Background and Aim: Adalimumab is administered and dosed using a standardized treatment regimen. Although therapeutic drug monitoring (TDM) may help optimize treatment efficacy, the lower cut‐off concentration of adalimumab needed to retain disease remission has not been established. This cross‐sectional study of patients with Crohn's disease on stable medication aimed to determine a lower therapeutic drug concentration threshold of adalimumab associated with biochemical disease remission. Methods: C‐reactive protein (CRP) and fecal calprotectin were used as established markers and albumin as an explorative marker of disease activity. Time since introduction, treatment interval, drug dosage, serum drug concentration and antidrug antibodies, disease duration, age, and sex were recorded. Results: The study included 101 patients who were divided into "active disease" and "remission" groups for inflammatory markers based on cut‐off levels of 5 mg/L for CRP and 50 mg/kg for fecal calprotectin. Cut‐off levels for albumin of 36.5 and 41.5 g/L were also added as further indicatives of remission. Receiver operating characteristic analysis found optimal thresholds for adalimumab associated with remission at 6.8–7.0 mg/L for the combination of CRP and fecal calprotectin and when combining CRP, fecal calprotectin, and albumin. Conclusions: In patients with Crohn's disease, serum adalimumab of at least 6.8 mg/L was associated with biochemical disease remission based on CRP and fecal calprotectin, supporting the use of TDM to ensure disease control. Albumin should be further tested in this setting. Abstract : In this article, we examined the lower adalimumab serum concentration levels found to be associated with biochemical remission in patients with Crohn's disease. Serum adalimumab level of at least 6.8 mg/L was associated with biochemical disease remission based on C‐reactive protein (CRP) and fecal calprotectin, supporting the use of therapeutic drug monitoring (TDM) to ensure disease control.